2'-(2-bromohexadecanoyl)-paclitaxel conjugate nanoparticles for the treatment of non-small cell lung cancer in an orthotopic xenograft mouse model - Peng L (Dove Medical Press, 2014)
Lei Peng,1 Allison N Schorzman,2 Ping Ma,1 Andrew J Madden,2 William C Zamboni,2–4 Soumya Rahima Benhabbour,1 Russell J Mumper1,4 1Center for Nanotechnology in Drug Delivery, Division of Molecular Pharmaceutics, UNC Eshelman School of Pharmacy, University of North Carolina at Chapel Hill, 2Division of Pharmacotherapy and Experimental Therapeutics, UNC Eshelman School of Pharmacy, University of North Carolina at Chapel Hill, 3Center for Pharmacogenomics and Individualized Therapy, University of North Carolina at Chapel Hill, 4UNC Lineberger Comprehensive Cancer Center, University of North Carolina at Chapel Hill, North Carolina, NC, USA Abstract: A nanoparticle (NP) formulation with 2'-(2-bromohexadecanoyl)-paclitaxel (Br-16-PX) conjugate was developed in these studies for the treatment of non-small cell lung cancer (NSCLC). The lipophilic paclitaxel conjugate Br-C16-PX was synthesized and incorporated into lipid NPs where the 16-carbon chain enhanced drug entrapment in the drug delivery system and improved in vivo pharmacokinetics. The electron-withdrawing bromine group was used to facilitate the conversion of Br-C16-PX to paclitaxel at the tumor site. The developed system was evaluated in luciferase-expressing A549 cells in vitro and in an orthotopic NSCLC mouse model. The results demonstrated that the Br-C16-PX NPs had a higher maximum tolerated dose (75 mg/kg) than Taxol® (19 mg/kg) and provided significantly longer median survival (88 days versus 70 days, P<0.05) in the orthotopic NSCLC model. An improved pharmacokinetic profile was observed for the Br-C16-PX NPs at 75 mg/kg compared to Taxol at 19 mg/kg. The area under the concentration versus time curve (AUC)0–96 h of Br-C16-PX from the NPs was 91.7-fold and 49.6-fold greater than Taxol in plasma and tumor-bearing lungs, respectively, which provided sustained drug exposure and higher antitumor efficacy in the NP-treated group. Keywords: tubulin polymerization, pharmacokinetic, maximum tolerated dose, efficacy, pleural fluid, bioluminescence imaging, A549 cell tumor model